The Effect of Reading Newspaper and Short Stories on Students’ Vocabulary Size at Cenderawasih University Setting - Wijayanti, Erfin (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This study aimed to investigating the effect of reading newspapers and short stories on students' vocabulary size and whether there is a significant difference between students who read newspapers and short stories at third semester of English Education Study Program in Cenderawasih University. The method of the research was quasi-experimental. The sample of the research was the students of third semester English Education Study Program at Cenderawasih University. It consisted of 36 students who were divided into two groups, i.e., Newspaper group and Short Story group, which were given the texts as a treatment based on their name's group. The test -2,000-VLT design of Nation- was used as the primary instrument test to measure the students' vocabulary size before and after given treatment. After analyzing the data, both groups demonstrated a significant increase in vocabulary size. The Newspapers group increased from 1,206 to 1,556 words, while the Short Story group shows the mean 1,134 words moved up to 1,469 words. However, the T-test shows that the vocabulary size of both the Newspaper group and Short Story group is not different significantly. Keywords: Effect, Vocabulary Size, Reading, Newspaper, Short Story